(3JShjb GdNOeGJ (B/s - (3GdMGL, Ydj Jhajb CMeOs; (3eMehO, SejQ MSjf s ((3YeGf(B: s (3OGQ GdGYUGQ(B, s, 2011)
(3ebOeI aj GdJQhjL GdJLGQj , GdJQhjL cYedjI EJUGd , Gdeaghe GdMOjK dEOGQI GdJShjb ,GdeRjL GdJShjbj ddNOeGJ , GdJObjb GdJShjbj , GdJShjb GdaYGd , GdJShjb gh LhOI GdMjGI , GSJQGJjLjI GdJQhjL , GdJShjb GdRQGYj (B.s
Keywords: (3COGQI GdeHjYGJs; (3GdJQhjL GdJLGQIs; (3GdJShjbs; (3GdNOeGJs; (3GdNOeGJ `` JShjbs